Technology Acceptance Model dalam Mendorong Intention to use pada Sistem Informasi Akuntansi - Tikaromah, Oom; Nurjanah, Nurjanah; Yahya, Adibah; Hidayat, Taufik (LPPM Universitas Pelita Bangsa, 2024)
This study aims to analyse the factors that influence the intention to use the Accounting Information System (AIS) in Indonesian construction companies using the Technology Acceptance Model (TAM). The research method used is quantitative involving 47 respondents who are employees involved in financial records. Data were collected through a questionnaire that measured perceptions of ease of use, usefulness, and attitudes towards the use of AIS. The results of the analysis show that perceived ease of use and attitude towards using have a positive and significant effect on intention to use, while perceived usefulness does not show a significant effect. These findings indicate that ease of use and positive attitude towards technology are key factors in encouraging the intention to use AIS. This research provides insights for companies in designing more effective technology adoption strategies, focusing on improving ease of use and developing positive attitudes among employees.